How JustAnswer Works:
  • Ask an Expert
    Experts are full of valuable knowledge and are ready to help with any question. Credentials confirmed by a Fortune 500 verification firm.
  • Get a Professional Answer
    Via email, text message, or notification as you wait on our site. Ask follow up questions if you need to.
  • Go back-and-forth until satisfied
    Rate the answer you receive.
Ask Sandhya_sharma Your Own Question
Sandhya_sharma
Sandhya_sharma, Master's Degree
Category: Pre-Calculus
Satisfied Customers: 10876
Experience:  I hold M.Sc and M.Phil degrees in math and have several years of teaching experience.
14910578
Type Your Pre-Calculus Question Here...
Sandhya_sharma is online now

T(x) = 2x-6 s(x) = 1/2x+3 s(t(x)) = s(2x-6) Where do I go

This answer was rated:

t(x) = 2x-6
s(x) = 1/2x+3s(t(x)) = s(2x-6)Where do I go from here. Do I just multiply 2x by a 1/2 and add 3 to -6? For the answer to be 1x-3?Thanks

working on it

s(t(x))

= s(2x- 6)

= 1/2(2x - 6) + 3

= x - 3 + 3

= x

Thus, s(t(x)) = x

Customer: replied 10 days ago.
Why does the 1/2 go outside the brackets?
Customer: replied 10 days ago.
Well I suppose my question is since it's 1/2x shouldn't it just affect the 2x?

s(t(x))

= s(2x- 6)

replace x by (2x-6) in definition of s(x)

= 1/2(2x - 6) + 3

Now simplify then

Sandhya_sharma and other Pre-Calculus Specialists are ready to help you
Customer: replied 10 days ago.
Ok thank you.